Pengaruh Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Pada Usaha Rumah Makan Fanila Foody House di Eran Batu Kecamatan Karasik Kabupaten Toraja Utara - Tasik, Trivia; Pongtuluran, Althon K.; Tahirs, Jemi Pabisangan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Trivia Tasik (2023). This study aims to determine the effect of service quality and price on purchasing decisions at Fanila Foody House Restaurant. This study uses a questionnaire distributed to consumers of Fanila Foody House. Sampling using non-probability sampling with a purposive sampling approach. The data analysis technique used is multiple linear regression analysis for service quality and price variables. From the test results it is known that service quality (X1) and price (X2) have a positive and significant effect on purchasing decisions (Y). The service quality variable tcount is 16,595 greater than ttable 2,010 (0,000 <0.05). The price variable tcount is 3,683 greater than ttable 2,010 (0.001 <0.05). Service Quality (X1) and Price (X2) show a calculated Fvalue of 142,879 greater thanÂ  table 4,050 with a sig. 0.000 < 0.05, it can be seen that the variable Service Quality (X1) and Price (X2) has a simultaneous effect on the Purchase Decision (Y).